Quantum Mechanics and an Ontology of Intersubjectivity: Perils and Promises - Pugliese, Marc A. (Open theology, 2018)
Contemporary theology has realized the importance of integrating what we know from the "new physics"-quantum mechanics and relativity theory-into the metaphysical and ontological categories used by theology to consider God, the world, and the God-world relationship. The categories of subjectivity and relationality have risen to prominence in these discussions. Both academic and popular presentations can obscure the vital distinction between what physicists agree on concerning quantum mechanics and the contested interpretation of quantum mechanics, or what quantum mechanics reveals about reality. After (1) summarizing the significant distinction between quantum mechanics per se and the interpretations of quantum mechanics and (2) the agreed upon quantum mechanical experimental procedure and its attendant mathematical formalism, as well as a few of the foremost interpretations, this paper (3) attempts a minimalist culling of some rudimentary but clear ontological principles and categories from what is agreed upon in quantum mechanics, without appeals-tacit or explicit-to one of the many controversial interpretations or to contestable philosophical assumptions and deductions, and these are: experience, subjectivity, relationship, and event. The paper closes by (4) commending one speculative scheme that is especially conducive to developing an interpretation of quantum mechanics consonant with the ontological principles and categories so derived, that of Alfred North Whitehead